Ferroptosis and oral squamous cell carcinoma: connecting the dots to move forward - Antonelli, Alessandro; Battaglia, Anna Martina; Sacco, Alessandro; Petriaggi, Lavinia; Giorgio, Emanuele; Barone, Selene; Biamonte, Flavia; Giudice, Amerigo (Frontiers in Oral Health, 2024)
Oral squamous cell carcinoma (OSCC) is an aggressive disease whose incomplete biological comprehension contributes to the inappropriate clinical management and poor prognosis. Thus, the identification of new promising molecular targets to treat OSCC is of paramount importance. Ferroptosis is a regulated cell death caused by the iron-dependent accumulation of reactive oxygen species and the consequent oxidative damage of lipid membranes. Over the last five years, a growing number of studies has reported that OSCC is sensitive to ferroptosis induction and that ferroptosis inducers exert a remarkable antitumor effect in OSCC, even in those displaying low response to common approaches, such as chemotherapy and radiotherapy. In addition, as ferroptosis is considered an immunogenic cell death, it may modulate the immune response against OSCC. In this review, we summarize the so far identified ferroptosis regulatory mechanisms and prognostic models based on ferroptosis-related genes in OSCC. In addition, we discuss the perspective of inducing ferroptosis as a novel strategy to directly treat OSCC or, alternatively, to improve sensitivity to other approaches. Finally, we integrate data emerging from the research studies, reviewed here, through in silico analysis and we provide a novel personal perspective on the potential interconnection between ferroptosis and autophagy in OSCC.